The income distribution in the UK: A picture of advantage and disadvantage - Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2015)
This chapter describes the UK income distribution and how it has evolved over the last 50 years. It also includes some comparisons with the income distributions of other rich countries. Multiple perspectives on the distribution are provided: there is evidence about real income levels and inequality, and the prevalence of affluence and of poverty.
Keywords: D31; I32; 330; inequality; poverty; affluence; income distribution; United Kingdom